2021
DOI: 10.1016/j.jwb.2021.101190
|View full text |Cite
|
Sign up to set email alerts
|

Financial crisis of 2008 and outward foreign investments from China and India

Abstract: Based on a cross-industry panel of 510 non-financial Indian and Chinese firms during the period 2005-2015, we argue and show that Chinese firms with resource and asset seeking motives and Indian firms with market-seeking motives suffered differently from the financial crisis of 2008. Specifically, Indian firms that faced financial market imperfections domestically and market contraction externally had to cut back on outward investments as markets shrank and sales growth dampened. In contrast, the fortunes of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…The authors of [36] studied the impact of protectionism of property rights on the behavior pattern of multinational companies, and found that institutional performance was strongly correlated with the FDI ratio to total domestic investment. The property right importance for FDI attraction has been confirmed by the study of [37].…”
Section: Literature Reviewmentioning
confidence: 67%
“…The authors of [36] studied the impact of protectionism of property rights on the behavior pattern of multinational companies, and found that institutional performance was strongly correlated with the FDI ratio to total domestic investment. The property right importance for FDI attraction has been confirmed by the study of [37].…”
Section: Literature Reviewmentioning
confidence: 67%
“…This study used this technique to control number of econometric issues related to estimation. The system GMM estimation technique controls several issues, such as autoregressive problem, heteroskedasticity, and potential endogeneity, and thus provides robust estimates (Arellano & Bond, 1991; Athreye et al, 2021; Roodman, 2009). Also, system GMM offers two sorts of robustness tests, that is, Hansen test and Arellano–Bond (AB) test, to determine the validity of results by checking whether estimation suffers from overidentification and serial correlation issues.…”
Section: Methodsmentioning
confidence: 99%
“…the country of origin would be associated with foreignness because the home country can provide the necessary support in the development of resources and capabilities (Athreye et al, 2021), creating the potential for institutional asymmetry between the home and host countries and enhancing FSAs unavailable to domestic rivals (Cuervo-Cazurra et al, 2018). Athreye et al (2021) also note that foreign investment of Chinese firms is mainly driven by assets built in domestic markets and studying China's Haier group shows that advantages associated with government support played important roles in internationalising.…”
Section: The Foreignness Effectmentioning
confidence: 99%
“…For instance, CMNEs of green energy and high tech industries favoured by China's 13th Five-Year National Plan development policy enjoy AOF when the host countries acknowledge China's support in terms of political aid, economic support, or philanthropic work from CMNEs (Cui and Jiang, 2012), resulting in the support of outward foreign direct investments (OFDIs) (He and Lyles, 2008;Li et al, 2014). Athreye et al (2021) suggest that government-related ownership advantages shape Chinese firms' level, location and type of overseas investment. Chinese overseas acquisitions are more commonly carried out due to country-specific government financial support.…”
Section: 22mentioning
confidence: 99%
See 1 more Smart Citation